2014
DOI: 10.1002/hep.26959
|View full text |Cite
|
Sign up to set email alerts
|

Type I and type III interferon-induced immune response: It's a matter of kinetics and magnitude

Abstract: See Articles on Pages 1250 and 1262 T he interferon (IFN) family of cytokines, including type I and III IFNs, represent a first line of defense that "interferes" with a vast range of viral infections.1 IFN cytokines are commonly classified into distinct families, based on their structural properties and on the receptor complex through which they signal.1 Type I IFNs, including IFN-b and -a, exert their biological activities through a heterodimeric receptor complex known as IFN-a receptor (IFNAR) that consists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 20 publications
(51 reference statements)
3
22
0
Order By: Relevance
“…In contrast, the restricted expression of IFN-λR1 prevented a direct action of IFN-λ on both NK cells and monocytes, with only responses observed on differentiated macrophages. This suggests that IFN-λ might play a more prominent role in tissue-specific responses as compared to the periphery, in line with other studies describing that IFN-λ1 has a more delayed and prolonged effect through activation of specific tissue-resident cells, specifically epithelial cells and hepatocytes [25,26]. TLR-dependent crosstalk between NK cells and macrophages has already been described in tissue-specific interactions in the liver.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In contrast, the restricted expression of IFN-λR1 prevented a direct action of IFN-λ on both NK cells and monocytes, with only responses observed on differentiated macrophages. This suggests that IFN-λ might play a more prominent role in tissue-specific responses as compared to the periphery, in line with other studies describing that IFN-λ1 has a more delayed and prolonged effect through activation of specific tissue-resident cells, specifically epithelial cells and hepatocytes [25,26]. TLR-dependent crosstalk between NK cells and macrophages has already been described in tissue-specific interactions in the liver.…”
Section: Discussionsupporting
confidence: 87%
“…The delayed activation of NK cells by IFN-λ, mediated through macrophage IL-12 production, could explain the observed differences in biological functions between the type I and type III IFNs in inflammatory responses, but also by differences in kinetics or sustainability of the response. It should be noted that a similar kinetic on innate immune response activation by type III IFNs has been previously described for DCs and hepatocytes [26,30,38].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Both IFN-beta and IFN-rhamda triggered a sustained ISG response; on the other hand, IFN-alpha produced a kinetic profile of genes that peaked early in the therapy and then rapidly decreased ( Figure 9). No significant difference was observed in STAT1 tyrosine phosphporylation levels between IFN-beta and IFN-alpha, where as serine phosphporylation at position 727 was stimulated more strongly by IFN-beta than by IFN-alpha [29]. The finding that IFN-beta invariably possessed the highest activity among Type I and Type III IFNs suggested that IFN-beta and IFN-rhamda-3 may have superior clinical activity.…”
Section: Discussionmentioning
confidence: 92%